The Difference of Using Antibiotics Before and After Antimicrobial Resistance Control Program (PPRA) at RSUP Dr. M. Djamil Padang - Ermawati, Ermawati; Khambri, Daan; Almasdy, Dedy (Fakultas Kedokteran Universitas Andalas, 2021)
Antibiotics have been proven to be beneficial for human life since their discovery. This type of drug is the most widely used in infections caused by bacteria. the function is to inhibit growth or kill microorganisms. Therefore, more than 30-80% of patients in developed countries who are hospitalized receive antibiotics, either alone or in combination. Evaluating the implementation of PPRA at RSUP. Dr. M. Djamil by comparing the evaluation of antibiotic use before and after the application of PPRA in inpatients in the Obgyn.We conducted this research including a type of correlational analytical research with a retrospective approach. The research sample was taken by the Medical Record room of the RSUP. Dr. M. Djamil Padang. The research was carried out for 1 month, from May 1 to May 31, 2020. The population in this research was all inpatients of Obstetrics and Gynecology in Dr. M. Djamil Padang.There was an increase in the percentage of antibiotic use in 2019 in line with the higher percentage of surgery in 2019 compared to 2018. As regulated by the guidelines for the use of antibiotics in Dr. M. Djamil, for surgery, prophylactic antibiotics are given 30 minutes before the procedure to prevent infection due to the invasive action. The use of prophylactic antibiotics whether to continue is determined by the type of operation, the length of the operation, the amount of bleeding during the operation, the clinical patient, the laboratory value.There were no significant changes in the implementation of PPRA's work on the qualitative analysis of antibiotic use.Keywords: Antibiotics, PPRA, Evaluation